False discoveries in mutual fund performance: Measuring luck in estimated alphas - Laurent Barras; Olivier Scaillet; Russ Wermers (University of Cologne, Centre for Financial Research (CFR), 2009)
This paper develops a simple technique that controls for false discoveries, or mutual funds that exhibit significant alphas by luck alone. Our approach precisely separates funds into (1) unskilled, (2) zero-alpha, and (3) skilled funds, even with dependencies in cross-fund estimated alphas. We find that 75% of funds exhibit a zero alpha (net of expenses), consistent with the Berk and Green (2004) equilibrium. Further, we find a significant proportion of skilled (positive alpha) funds prior to 1996, but almost none by 2006. We also show that controlling for false discoveries substantially improves the ability to find funds with persistent performance.
Keywords: G11; G23; C12; 330; Mutual Fund Performance; Multiple-Hypothesis Test; Luck; False Discovery Rate